2003
DOI: 10.1029/2002rg000121
|View full text |Cite
|
Sign up to set email alerts
|

Review of mesospheric temperature trends

Abstract: International audienceIn recent times it has become increasingly clear thatreleases of trace gases from human activity have a potentialfor causing change in the upper atmosphere. However,our knowledge of systematic changes and trends inthe temperature of the mesosphere and lower thermosphereis relatively limited compared to the Earths loweratmosphere, and not much effort has been made to synthesizethese results so far. In this article, a comprehensivereview of long-term trends in the temperature of the regionf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
291
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 240 publications
(323 citation statements)
references
References 184 publications
27
291
3
2
Order By: Relevance
“…[19] The increase in greenhouse gas concentrations also produces long-term variation in the E-region temperature [Aikin et al, 1991;Akmaev and Fomichev, 1998;Beig et al, 2003;Lastovicka et al, 2006a] and diurnal tidal amplitude [Bremer et al, 1997;Baumgaertner et al, 2005]. Temperature trends may affect Sq through the collision frequency and tidal amplitude trends through the V × B term in J.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The increase in greenhouse gas concentrations also produces long-term variation in the E-region temperature [Aikin et al, 1991;Akmaev and Fomichev, 1998;Beig et al, 2003;Lastovicka et al, 2006a] and diurnal tidal amplitude [Bremer et al, 1997;Baumgaertner et al, 2005]. Temperature trends may affect Sq through the collision frequency and tidal amplitude trends through the V × B term in J.…”
Section: Discussionmentioning
confidence: 99%
“…von Savigny et al, 2004); (b) the extensive latitude coverage of both ACE-FTS and SABER makes them a potentially very valuable resource as a transfer standard for inter-comparison of temperatures obtained by different techniques and from observation stations at different locations; (c) the annual average temperature of the atmosphere in the region of the mesopause has changed very little over the past decade (e.g. Beig et al, 2003); (d) the averaged altitude of emission of the OH Meinel bands has been found to be remarkably consistent (87 km in altitude and a width at half intensity of 8-10 km) (e.g. She and Lowe, 1998;Oberheide et al, 2006) since the seminal report on the topic by Baker and Stair in 1988; (e) the quality and volume of data available in the datasets is sufficient for a useful statistical comparison; (f) similar efforts are currently underway for the results from other ground-based instruments (Oberheide et al, 2006;López-González et al, 2007); (g) temperatures derived from OH emissions are beginning to be used in the study of long term change in the mesosphere and lower thermosphere (Bittner et al, 2002;Sigernes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Model studies of the climate change induced by increasing CO 2 have traditionally considered only the effect of the 15 mm band (see review by Beig et al [2003]). With the CO 2 concentration increased, the cooling rate provided by this band also increases and results in cooling of the middle atmosphere.…”
Section: Model Resultsmentioning
confidence: 99%